ESC e-Cardiology Working Group Position Paper: Overcoming challenges in digital health implementation in cardiovascular medicine. (July 2019) - Frederix, Ines; Caiani, Enrico G; Dendale, Paul; Anker, Stefan; Bax, Jeroen; Böhm, Alan; Cowie, Martin; Crawford, John; de Groot, Natasja; Dilaveris, Polychronis; Hansen, Tina; Koehler, Friedrich; et al.
Cardiovascular disease is one of the main causes of morbidity and mortality worldwide. Despite the availability of highly effective treatments, the contemporary burden of disease remains huge. Digital health interventions hold promise to improve further the quality and experience of cardiovascular care. This position paper provides a brief overview of currently existing digital health applications in different cardiovascular disease settings. It provides the reader with the most relevant challenges for their large-scale deployment in Europe. The potential role of different stakeholders and related challenges are identified, and the key points suggestions on how to proceed are given. This position paper was developed by the European Society of Cardiology (ESC) e-Cardiology working group, in close collaboration with the ESC Digital Health Committee, the European Association of Preventive Cardiology, the European Heart Rhythm Association, the Heart Failure Association, the European Association of Cardiovascular Imaging, the Acute Cardiovascular Care Association, the European Association of Percutaneous Cardiovascular Interventions, the Association of Cardiovascular Nursing and Allied Professions and the Council on Hypertension. It relates to the ESC's action plan and mission to play a pro-active role in all aspects of the e-health agenda in support of cardiovascular health in Europe and aims to be used as guiding document for cardiologists and other relevant stakeholders in the field of digital health.